2018
DOI: 10.14295/2238-6416.v73i2.686
|View full text |Cite
|
Sign up to set email alerts
|

Influência do tipo de fermento nas características físico-químicas de queijo Minas artesanal do serro – Minas Gerais, maturado em condições controladas

Abstract: Na produção do queijo Minas artesanal do Serro são utilizados leite cru, coalho e fermento lático natural, designado de “pingo”. Alguns produtores da região do Serro, fazem uso da “rala”, parte ralada do próprio queijo artesanal, com 3 a 5 dias de fabricação, que é adicionada ao leite em substituição ao “pingo”. Sabendo-se que condições controladas de umidade relativa do ar (UR) e temperatura também podem influenciar as características dos queijos durante a maturação. O objetivo deste trabalho foi avaliar a in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 4 publications
1
1
0
1
Order By: Relevance
“…The enzymatic activity in cheese ripening comes from the rennet retained in cheese curd, from native milk enzymes and also from bacteria present in pingo and raw milk. These enzymes release alkaline nitrogen compounds from protein degradation, increasing the pH of cheese (Vale et al, 2018), as occurred in the present study.…”
Section: Resultssupporting
confidence: 72%
“…The enzymatic activity in cheese ripening comes from the rennet retained in cheese curd, from native milk enzymes and also from bacteria present in pingo and raw milk. These enzymes release alkaline nitrogen compounds from protein degradation, increasing the pH of cheese (Vale et al, 2018), as occurred in the present study.…”
Section: Resultssupporting
confidence: 72%
“…This difference occurred because the samples collected and analyzed by these researchers had three to six days of ripening, which is a reduced time for the development of secondary proteolytic activity in cheeses. On the other hand, for samples of cheese from the Serro region, Vale et al (2018) reported ripening times between 3 and 31 days between 10.19% and 22.68% for RD, and Chaves et al (2016) observed SNT values between 0.188% and 0.611%. According to these authors, the variation observed demonstrates that these indexes tend to increase over ripening time and that secondary proteolysis occurs gradually (Law and Tamime, 2010;Dores et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…Besides the type of yeast, another factor that can affect the cheese characteristics is the maturation condition. This is influenced by two fundamental elements: temperature and relative air humidity, which may interfere in both microbial growth and sensory characteristics (Vale, Rodrigues, & Martins, ). However, it seems that the altitude was not clearly related to the sensory aspects (Bambuí—706 m; Medeiros—922 m; Tapiraí—673 m; São Roque—819 m; Vargem Bonita—740 m; Araxá—1,008 m; Ibiá—914 m; Sacramento—832 m).…”
Section: Discussionmentioning
confidence: 99%